1975
DOI: 10.1152/ajplegacy.1975.229.3.754
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vascular and myocardial responses to carotid body stimulation in the dog

Abstract: Coronary vascular and myocardial responses to selective hypoxic and/or hypercapnic carotid chemoreceptor stimulation were investigated in constantly ventilated, pentobarbital or urethan-chloralose anesthetized dogs. Bilaterally isolated carotid chemoreceptors were perfused with autologous blood of varying O2 and CO2 tensions via an extracorporeal lung circuit. Systemic gas tensions were unchanged. Effects of carotid chemoreceptor stimulation on coronary vascular resistance, left ventricular dP/dt, and strain-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The STD AMP factors showed that the molecular structure of each ligand affects the epitope mapping of each proton. Their preference for Sudlow site I as it was derived from the competitive STD NMR experiments confirms the existing literature data 46,49,59 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The STD AMP factors showed that the molecular structure of each ligand affects the epitope mapping of each proton. Their preference for Sudlow site I as it was derived from the competitive STD NMR experiments confirms the existing literature data 46,49,59 .…”
Section: Discussionsupporting
confidence: 87%
“…Herein, we used this method for mapping of the interacting epitopes of each of the three ligands with BSA. To our knowledge, no STD NMR experiments have been reported for rosmarinic and salvianic acid 59 . The simultaneous evaluation of the interaction profile of rosmarinic acid and its constituents could provide a global view on the driving forces that each component contributes to the final interaction on the integral compound.…”
Section: Discussionmentioning
confidence: 98%
“…23 The stimulation of these receptors could lead to pain and autonomic changes. 24 Accordingly, the blockage of these receptors by local anesthetics could provide somatic and visceral analgesic effects. 20,23 There is no consensus on the volume and concentration of local anesthetics used in the QLB.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ehrhart et al (10) found a slight increase in left ventricular (LV)l dPldt and slight decrease in LV contractile force, whereas Stern and Rapaport (11) indicated that the aortic chemoreceptor reflex induced positive inotropic effects but the carotid chemoreceptor reflex induced no inotropic effect. It must be pointed out that all of these studies (5)(6)(7)(8)(9)(10)(11) have been performed in anesthetized animal preparations, where the unknown mitigating effects of the anesthetic and general surgery play an undetermined role in the interpretation of these data.…”
Section: Introductionmentioning
confidence: 99%